The impact of age on survival in stage II colon cancer: a SEER database analysis stratified by chemotherapy status - Zou, Zhengrong; Tang, Xin; Hong, Xinping; Zou, Lingting (Translational Cancer Research, 2026)
Background: XXXXXXXXXXX. This study aimed to evaluate the impact of age on survival outcomes in stage II colon cancer, with a specific focus on comparing patients who received chemotherapy vs. those who did not.Methods: We conducted a retrospective analysis of data from the SEER database, including patients diagnosed with stage II colon cancer between 2000 and 2020. The study cohort was stratified by chemotherapy treatment status. Kaplan-Meier estimators and multivariate Cox regression models were employed to analyze survival outcomes, with adjustments for sociodemographic, clinicopathological, and treatment-related factors.Results: The study included 24,043 patients diagnosed with stage II colon cancer, among whom 658 were under 40 years of age. Younger patients exhibited a higher prevalence of poorly differentiated/undifferentiated carcinomas and advanced T-stage disease, and were more frequently treated with chemotherapy. Age was identified as a significant predictor of overall survival in both chemotherapy-treated and non-treated groups, with a more pronounced effect observed in the latter. Multivariate analysis demonstrated a progressive increase in mortality risk with advancing age, using the youngest cohort (